2021
DOI: 10.3906/sag-2005-82
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine plus azithromycin and early hospital admission are beneficial in COVID-19 patients: Turkish experience with real-life data

Abstract: Background/aim New treatment regimens for COVID-19, which has threatened the world recently, continue to be investigated. Although some of the treatments are promising, it is thought to be early to state that there is definitive treatment. Experiences and treatment protocol studies from treatment centers are still important. The aim of this study is to evaluate factors affecting the treatment process of the first cases followed in our clinic. Materials and methods The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…Four studies did not find significant association between the infection severity and the patients' comorbidities (30)(31)(32)(33). Tanriverdi et al study only found the overall significant association of all comorbidities combined with the infection severity (27). The most common initial symptoms reported were high fever, dry cough, and dyspnea.…”
Section: Study Characteristicsmentioning
confidence: 94%
See 1 more Smart Citation
“…Four studies did not find significant association between the infection severity and the patients' comorbidities (30)(31)(32)(33). Tanriverdi et al study only found the overall significant association of all comorbidities combined with the infection severity (27). The most common initial symptoms reported were high fever, dry cough, and dyspnea.…”
Section: Study Characteristicsmentioning
confidence: 94%
“…Various comorbidities were assessed and compared between two groups, except Medetalibeyoglu et al and Zheng et al studies which did not assess comorbidities of the subjects (12,13). The comorbidities that were more significantly common in the severe groups included cardiovascular diseases (i.e., coronary artery disease, heart failure) in ten studies (14-24), hypertension in nine studies (14, 16-19, 21, 22, 24, 25), chronic respiratory diseases in nine studies (17,19,20,(23)(24)(25)(26)(27)(28), diabetes mellitus in seven studies (11,16,18,21,22,25,29), cerebrovascular diseases in five studies (15,16,18,21,24), chronic kidney disease in four studies (18,(22)(23)(24), cancer in one study (25), and immunosuppression in one study (17). Four studies did not find significant association between the infection severity and the patients' comorbidities (30)(31)(32)(33).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The included studies were conducted in various regions, such as American, 11,13,14,17,[22][23][24] European, 10,12,15,16,20,21 and Middle East countries. 18,19,25,26 All of the studies recruited adults with age ranging from 45-83 years old. Included patients also revealed common underlying conditions, such as hypertension, diabetes mellitus, chronic obstructive pulmonary disease and cardiovascular disease.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…9 Yet, several clinical trials have shown conflicting results and it is not clear whether the available evidence is in favour or against the use of Azithromycin in COVID-19 patients. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Therefore, we design a systematic review of existing clinical studies and perform a meta-analysis to further investigate and measure the efficacy and safety of Azithromycin in COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%
“…3 Although several researches have been conducted to investigate the usage of hydroxychloroquine in decreasing the mortality rate, there are still arguments in its result. 6 A study conducted in Turkey showed that combining hydroxychloroquine with azithromycin could increase its effectiveness and decrease patients' length of stay in hospital. 6 Azithromycin, a macrolide antibiotic, has in vitro antiviral properties such as decreasing viral replication, blocking entrance into host cells, and a potential immunomodulating effect.…”
Section: Introductionmentioning
confidence: 99%